Analisis Pengaruh Jumlah Penduduk Dan Pdrb Per Kapita Terhadap Disparitas Pendapatan Klaster Metropolitan Provinsi Jawa Timur - Irfandi Liestiawan (MDP Student Conference, 2026)
This study examines how population size and GRDP per capita influence income disparity in East Java’s Metropolitan Cluster from 2020 to 2024. Inequality is salient because the cluster is a growth engine yet continues to face uneven income distribution. A descriptive quantitative approach is employed using panel data that combine time-series and cross-sectional observations from seven member regencies/municipalities. Income disparity is measured by the Gini ratio as the dependent variable, while the independent variables are population and GRDP per capita. Random Effects Model (REM) estimation indicates that population has no significant effect on income disparity, whereas GRDP per capita has a positive and significant effect. Jointly, both variables significantly affect income disparity. The findings suggest that growth reflected in higher GRDP per capita may widen inequality, underscoring the need for more inclusive regional development policies so benefits are shared more evenly.